Penerapan Model Problem Based Learning dengan Pendekatan Kontekstual dalam Meningkatkan Pemecahan Masalah Matematis Siswa - Rosa Septiana Indriyani; Supandi Supandi; Sulthon Al Mujadidi (Journal on Education, 2024)
The aim of learning mathematics includes the ability to effectively tackle mathematical challenges. By honing their problem-solving abilities, students can enhance their critical thinking rather than simply focusing on the final answers. This study endeavors to enhance students' proficiency in solving mathematical problems through the application of a problem-based learning approach within a contextual framework. The research methodology employed here is Classroom Action Research (CAR), conducted across two cycles involving grade XI.5 students at SMA Negeri 9 Semarang during the 2023/2024 academic year. The research utilized a problem-solving assessment instrument alongside observational data collected during the learning process. The test results served as a gauge for students' problem-solving skills. Significant progress was noted across both cycles, with the first cycle achieving a 60% pass rate and an average score of 78.14, while the second cycle saw a notable increase in pass rate to 94.28% and an average score of 95.63. The overall improvement in pass rates across both cycles underscores the efficacy of employing a problem-based learning model with a contextual approach in advancing students' mathematical problem-solving abilities.